Nonsurgical endodontic retreatment of fused teeth with transposition: a case report - Miguel Agostinho Beco Pinto Cardoso; Rita Brandão Noites, Miguel André Duarte Martins; Manuel Pedro da Fonseca Paulo (Korean Academy of Conservative Dentistry, 2016)
Tooth transposition is a disorder in which a permanent tooth develops and erupts in the normal position of another permanent tooth. Fusion and gemination are developmental disturbances presenting as the union of teeth. This article reports the nonsurgical retreatment of a very rare case of fused teeth with transposition. A patient was referred for endodontic treatment of her maxillary left first molar in the position of the first premolar, which was adjacent to it on the distobuccal side. Orthopantomography and periapical radiography showed two crowns sharing the same root, with a root canal treatment and an associated periapical lesion. Tooth fusion with transposition of a maxillary molar and a premolar was diagnosed. Nonsurgical endodontic retreatment was performed. At four yr follow-up, the tooth was asymptomatic and the radiolucency around the apical region had decreased, showing the success of our intervention. The diagnosis and treatment of fused teeth require special attention. The canal system should be carefully explored to obtain a full understanding of the anatomy, allowing it to be fully cleaned and obturated. Thermoplastic techniques were useful in obtaining hermetic obturation. A correct anatomical evaluation improves the set of treatment options under consideration, leading to a higher likelihood of esthetically and functionally successful treatment.